Devonian Lingulichnus and in situ lingulids: Taphonomy and paleoenvironments of preservation - Horodyski, Rodrigo Scalise; Netto, Renata Guimarães; Sedorko, Daniel (Palaeoworld, 2025)
Lingulids are significant infaunal elements of Lower to Middle Devonian in the Paraná Basin, Brazil, with Lingulichnus traces sometimes found in association with in situ lingulids specimens (Lingulida, Brachiopoda). These trace fossils are typically confined to offshore and transitional offshore-to-lower shoreface environments. This study investigates the relationship between Lingulichnus and in situ lingulids, explores their depositional and paleobiological implications. Four taphonomic modes were identified: (i) autochthonous — in situ, isolated lingulids normally associated with Lingulichnus verticalis or L. inclinatus; (ii) allochthonous — lingulids with reworking evidence (e.g., disarticulated or fragmented shells); (iii) autochthonous sub-primary position — in situ lingulids associated to Lingulichnus hamatus; (iv) temporary sub-primary position — in situ lingulids, isolated or associated to L. hamatus or L. verticalis. Except for the former, these taphonomic modes present high paleoecological resolution, and therefore, paleobiological implications. The in situ lingulids, with small size (≤ 1 cm), occur associated with Lingulichnus, suggesting fast burial under high sedimentation rates, and are concentrated in initial transgressive systems tracts in the study area. In this way, isolated in situ lingulids or associated with Lingulichnus can be a good indicator of high sedimentation rates, and demonstrate the preferential preservation of small organism unable to escape from the fast burial.